2022
DOI: 10.1007/s10067-022-06227-7
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in the light of the COVID-19 pandemic: infection, vaccination, and impact on disease management

Abstract: Patients with systemic lupus erythematosus (SLE) form a vulnerable group in terms of the impact of the COVID-19 pandemic on disease management. We conducted this overview by searches through Medline/PubMed, Scopus, and the Directory of Open Access Journals (DOAJ). The prevalence and severity of COVID-19, efficacy of COVID-19 vaccination, impact on the management of SLE, and the attitudes of SLE patients to COVID-19 and vaccination were explored. After screening and due exclusions, 198 studies were included for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 100 publications
(132 reference statements)
2
29
1
Order By: Relevance
“…The presence of comorbidities, organ related damages, intrinsic immune failure and immunosuppressive treatment amplify the concern of medical practitioners related to these patients [ 14 , 15 ]. The immune dysregulation of the interferon pathway encountered in SLE is another reason of concern, mainly because of its role in the innate immune response during the new coronavirus infection [ 14 , 15 , 16 ].…”
Section: Epidemiology and Risk Factors For Covid-19mentioning
confidence: 99%
“…The presence of comorbidities, organ related damages, intrinsic immune failure and immunosuppressive treatment amplify the concern of medical practitioners related to these patients [ 14 , 15 ]. The immune dysregulation of the interferon pathway encountered in SLE is another reason of concern, mainly because of its role in the innate immune response during the new coronavirus infection [ 14 , 15 , 16 ].…”
Section: Epidemiology and Risk Factors For Covid-19mentioning
confidence: 99%
“…Current evidence suggests that disease activity itself is a factor associated with a worse outcome in COVID-19 and the discontinuation of immunosuppressive medications is not recommended, although glucocorticoids should always be used in the lowest possible dose. 43 The Global Rheumatology Alliance analyses also demonstrated that individuals not receiving treatment for their SLE at the time of COVID-19 diagnosis had poorer outcomes, probably multifactorial, lack of access to SLE care or treatment, or poor adherence with medications. 32 Telemedicine, a strategy that enables the prevision of medical services remotely and that ensures social distancing, increased exponentially during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Together, even long-term inhibition of BAFF does not seem to be associated with significant increases in the rates of infections, although exposures to plasmodium falciparum or other important (sub-)tropical parasites may have been rare in these studies. Interestingly, COVID-19 outcomes have been more favorable in the small subset of patients with SLE treated with belimumab ( 45 , 46 ).…”
Section: Infectious Complications With Anti-baff and Anti-ifnar1mentioning
confidence: 99%
“…More patients treated with belimumab developed serious depression, treatment-emergent suicidality, sponsoradjudicated serious suicide, or self-injury events (44). On the other hand, severe COVID-19 outcomes in individuals with SLE were favorable with belimumab (45,46). Unlike anti-BAFF, anti-IFNAR1 significantly increased the rates of certain viral infections such as HZ and perhaps influenza, a finding that connects well with its mechanism-of-action that blocks a key element of antiviral immunity.…”
Section: Risk-benefit Assessments For the Use Of Anti-baff And Anti-i...mentioning
confidence: 99%